Anatomy and development of gynoecium in Tapiscia sinensis Oliv. and its implications for the origin of carpels (Bangladesh Journal of Botany, 2019)
Tapiscia sinensis Oliv. (Tapisciaceae) is a rare tree endemic in China. Characteristic of its androdioecy is the coexistence of male and hermaphroditic flowers. Its bisexual flower bears five stamens surrounding the gynoecium, which is composed of a terminal style and an ovary at the base. The style has a bifid stigmata, which is hollow and longer than stamens. The ovary is syncarpous, unilocular, formed by two fused carpels, with a basal or subbasal placenta. Ovule is bitegmic, anatropous, borne on the placenta and supplied by an amphicribral vascular bundle arising directly from receptacle. The carpel wall is supplied by a collateral vascular bundle. The ovule’s position changes from initially inserted on the ovary base to later attached to the middle of the ovary wall due to unequal growth of the embryo sac. Based on the present observation and others, the implications of vascular system in Tapiscia for the evolution of carpel are discussed.